Game Analysis of Supply Chain Enterprises’ Choice of Carbon Emission Reduction Behavior under Environmental Regulation and Consumers’ Low Carbon Preference - Huanhuan Huo; Haiyan Liu; Xinzhong Bao; Wei Cui (Discrete Dynamics in Nature and Society)
Under the background of low-carbon economy, in order to explore the internal mechanism of enterprises implementing carbon emission reduction behavior, this paper uses evolutionary game theory and numerical simulation method to study the evolutionary stability strategy and its influencing factors of carbon emission reduction behavior of supply chain enterprises in a two-level supply chain composed of a single supplier and a single manufacturer from a dynamic perspective, considering environmental regulation and consumers’ preference for low carbon emission. The results show that there are certain conditions that make supply chain enterprises converge to carbon emission reduction investment behavior under the effect of command-and-control environmental regulation and consumer low-carbon preference, and converge to cooperative carbon emission reduction behavior under the effect of market-based environmental regulation and consumer low-carbon preference. On this basis, the factors significantly influence the carbon emission reduction investment behavior of supply chain enterprises are the carbon emission reward and punishment coefficient and the low carbon preference coefficient of consumers. Increasing the carbon tax rate, carbon emission trading price and the proportion of cost subsidies, as well as encouraging consumers to consume low-carbon products will help promote the realization of cooperative carbon emission reduction.